Human resources development of young researchers: Case study at the Vietnam Academyof Social Sciences - Hoang, Xuan Sang (Khoa Quốc tế, ĐHQGHN, 2019)
Based on the theoretical framework of the researchers, the thesis has the theoretical basis for development, human resource development, human resources and young researchers. The thesis has identified the factors that influence the development of young human resources, especially the research environment is young researchers within Vietnam Academy of Social Sciences in particular.